Manufacturing method of enameled wire resistant to high-frequency voltage and product thereof
By performing plasma etching and multi-layer coating process on the surface of the conductor, combined with laser polishing, the problems of poor resistance to high temperature and high frequency voltage resistance are solved, and the manufacturing of high-performance enameled wire is realized to meet the needs of high-end motors and electrical appliances.
Patent Information
- Application Number
- CN202510657122.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-07-29
AI Technical Summary
The high-temperature resistance and high-frequency voltage resistance of traditional enameled wires are poor, making it difficult to meet the high-voltage, high-frequency, high-efficiency, energy-saving and compact development needs of high-tech motors, electrical appliances and transformers.
The surface of the conductor is treated with plasma etching to form the main coating, intermediate coating and outer coating. Through composite coatings and multi-stage curing processes, combined with laser polishing treatment, the interface bonding and coating adhesion are enhanced, and the insulation, thermal conductivity and mechanical properties are optimized using modified nanofillers and resin materials.
It significantly improves the insulation performance, high frequency resistance, high temperature resistance, thermal conductivity and mechanical properties of enameled wire, reduces dielectric loss, and is suitable for high-end fields such as new energy vehicle drive motors, wind power converters and 5G base station power supplies.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of enameled wires, and particularly relates to a manufacturing method and product of an enameled wire resistant to high-frequency voltage. Background Art
[0002] With the continuous development of high-tech nano materials, currently motors, electrical appliances, transformers, etc. at home and abroad are developing towards the trends of high voltage, high frequency, high efficiency, energy saving, and compactness, which has promoted the development of the electromagnetic wire industry from ordinary enameled wires to high-performance enameled wires. To meet the working requirements of motors, the enameled wires used must have the properties of high temperature resistance and high-frequency voltage resistance. However, the conductors of traditional enameled wires are generally round wires or flat wires, the insulating paint has a single function, and the preparation process is relatively simple, resulting in the unsatisfactory high temperature resistance and high-frequency voltage resistance of the produced enameled wire products, and there is still a large room for improvement. Summary of the Invention
[0003] To solve the technical problems existing in the prior art, the purpose of the present invention is to provide a manufacturing method and product of an enameled wire resistant to high-frequency voltage.
[0004] To achieve the above purpose and reach the above technical effects, the technical solution adopted by the present invention is as follows:
[0005] A manufacturing method of an enameled wire resistant to high-frequency voltage, comprising the following steps:
[0006] 1) Conductor pretreatment: performing plasma etching treatment on the surface of the conductor;
[0007] 2) Coating the main coating on the surface of the conductor obtained in step 1) to form the main coating;
[0008] 3) Coating the intermediate coating on the surface of the main coating obtained in step 2) to form the intermediate coating;
[0009] 4) Coating the outer coating on the surface of the intermediate coating obtained in step 3) to form the outer layer;
[0010] 5) Post-treatment: performing laser polishing treatment on the surface of the outer layer.
[0011] Further, in step 1), the etching gas is a mixed gas of argon and oxygen with a volume ratio of 2 - 3:1, the etching power is 200 - 600W, the treatment time is 20 - 60s, and the surface roughness Ra of the conductor reaches 0.6 - 1.5μm.
[0012] Further, in step 2), the preparation raw materials of the main coating include the following components in parts by weight:
[0013] 80 - 92 parts of polyimide resin;
[0014] 8 - 20 parts of modified nano - fillers.
[0015] Furthermore, the particle size of the modified nano - fillers is 20 - 90 nm, and the modified nano - fillers are a mixture of nano - barium titanate particles modified by a silane coupling agent and nano - titanium nitride particles.
[0016] Furthermore, in step 2), for coating the main coating on the surface of the conductor obtained in step 1), the steps of forming the main coating include:
[0017] Ultrasonically disperse the polyimide resin and the modified nano - fillers evenly, then coat them on the surface of the conductor, with the coating thickness being 12 - 20 μm, and cure them using a stepped high - temperature curing process:
[0018] The first stage: 240 - 260 °C, pre - cure for 2 - 6 min;
[0019] The second stage: 300 - 350 °C, final - cure for 10 - 20 min.
[0020] Furthermore, in step 3), for coating the intermediate coating on the surface of the main coating obtained in step 2), the steps of forming the intermediate coating include:
[0021] Mix the polyurethane resin and the fluorine - containing epoxy resin with a fluorine content of 10% - 20% evenly by mass ratio of 5 - 8:2 - 3 to obtain a mixed resin, then add an azobisisobutyronitrile initiator, continue to mix evenly, coat it on the surface of the main coating, and cure it through a UV - hot air dual - curing process:
[0022] Ultraviolet wavelength 365 nm, irradiation intensity 300 - 600 mW / cm 2 Irradiate for 2 - 5 min, and then hot - air cure at 140 - 170 °C for 8 - 12 min to form an intermediate layer with a thickness of 6 - 12 μm.
[0023] Furthermore, in step 4), for coating the outer layer coating on the surface of the intermediate coating obtained in step 3), the steps of forming the outer layer include:
[0024] Mix the polyesterimide resin and polyphenylene sulfide evenly by mass ratio of 5 - 10:2 - 4, add modified nano - mica flakes as a reinforcing phase, and form an outer layer with a thickness of 5 - 8 μm through an electrostatic atomization spraying process, with the spraying voltage being 20 - 50 kV, and the curing conditions being 180 - 240 °C, circulating hot - air curing for 20 - 40 min under nitrogen protection.
[0025] Furthermore, the thickness of the modified nano - mica flakes ≤50 nm, and the aspect ratio ≥50.
[0026] Furthermore, in step 5), the laser wavelength is 1064 nm, and the power density is 10 - 25 J / cm 2, the scanning speed is 100 - 200 mm / s, making the surface finish of the outer layer Ra ≤ 0.1 μm.
[0027] The present invention also discloses an enameled wire resistant to high-frequency voltage prepared by the manufacturing method of an enameled wire resistant to high-frequency voltage.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] The present invention discloses a manufacturing method of an enameled wire resistant to high-frequency voltage and its product. By performing plasma etching treatment on the conductor, the interfacial bonding force between the conductor and the subsequently formed coating can be enhanced, significantly improving the adhesion of the coating; by forming a main coating, an intermediate coating, and an outer layer on the surface of the conductor, it is beneficial to improve the insulation performance, high-frequency resistance performance, high-temperature resistance performance, thermal conductivity performance, and mechanical performance of the enameled wire, reduce dielectric loss and energy loss, and can be adapted to high-frequency application scenarios of 200 kHz and above, meeting the urgent needs of high-end fields such as new energy vehicle drive motors (800V high-voltage platform), wind power converters, and 5G base station power supplies for high-frequency insulating materials. Detailed Embodiments
[0030] The following elaborates on the present invention in detail so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0031] The following gives a brief overview of one or more aspects to provide a basic understanding of these aspects. This overview is not an exhaustive survey of all conceived aspects, and neither is it intended to identify key or decisive elements of all aspects nor to define the scope of any or all aspects. Its sole purpose is to present some concepts of one or more aspects in a simplified form as a prelude to the more detailed description that follows.
[0032] The present invention discloses a manufacturing method of an enameled wire resistant to high-frequency voltage, aiming to meet the high-frequency voltage requirements of enameled wire products in new energy motors and improve the high-frequency resistance performance of the products.
[0033] A manufacturing method of an enameled wire resistant to high-frequency voltage includes the following steps:
[0034] 1) Conductor pretreatment: Perform plasma etching treatment on the surface of the copper conductor. The etching gas is a mixed gas of argon and oxygen (volume ratio 2 - 3:1), the etching power is 200 - 600 W, and the treatment time is 20 - 60 s, making the surface roughness Ra of the copper conductor reach 0.6 - 1.5 μm; this step can enhance the interfacial bonding force between the copper conductor and the subsequently formed coating through plasma etching technology, significantly improving the adhesion of the coating, thereby avoiding the occurrence of phenomena such as coating peeling.
[0035] 2) Application of the main coating: Blend polyimide resin and modified nano-fillers at a weight ratio of 80 - 92:8 - 20 to form a composite coating. After ultrasonic dispersion to make it uniform, coat it on the surface of the copper conductor with a coating thickness of 12 - 20 μm. Use a stepped high-temperature curing process for curing:
[0036] The first stage: 240 - 260 °C, pre-cure for 2 - 6 min;
[0037] The second stage: 300 - 350 °C, final cure for 10 - 20 min;
[0038] In this step, the particle size of the modified nano-fillers is 20 - 90 nm. The modified nano-fillers are a mixture of nano-barium titanate particles modified by a silane coupling agent and nano-titanium nitride particles, and the mass ratio of nano-barium titanate particles to nano-titanium nitride particles is 1 - 3:2 - 5. In the present invention, polyimide resin and modified nano-fillers are compounded. Modification by a silane coupling agent is beneficial to enhancing the interfacial bonding force between the modified nano-fillers and polyimide resin, reducing particle agglomeration, reducing interfacial defects, improving the denseness of the main coating, blocking moisture penetration, and preventing deterioration of dielectric properties caused by moisture absorption of the coating under high-frequency electric fields. Polyimide resin has good high-temperature resistance and flexibility, but poor thermal conductivity. By compounding nano-titanium nitride particles with high thermal conductivity, high heat conductivity, and high conductive shielding, which are dispersed in the polyimide resin as heat conduction paths, the overall thermal conductivity and high-temperature resistance of the main coating can be significantly improved, the Joule heat accumulation under high-frequency electric fields can be reduced, the high-frequency eddy current loss can be decreased, and the synergistic effect of heat conduction and heat dissipation can be achieved. At the same time, the dielectric properties and mechanical properties can be optimized, the scratch resistance and wear resistance of the main coating can be improved, the formation of a conductive network can be avoided through nano-scale dispersion, the dielectric loss of the main coating can be significantly reduced, and the matching degree of the coating characteristic impedance with the copper conductor can be improved by dielectric regulation of nano-barium titanate particles, and the dielectric constant of the main coating can be adjusted to 3.5 - 4.5 to match the high-frequency impedance and reduce the electromagnetic wave reflection loss. Staged curing can improve the crystallinity of the main coating, and the interfacial bonding force can be enhanced by combining with plasma etching technology.
[0039] 3) Application of the intermediate coating: Mix polyurethane resin and fluorine-containing epoxy resin (fluorine content 10% - 20%) at a mass ratio of 5 - 8:2 - 3 to obtain a mixed resin, and then add azobisisobutyronitrile initiator (accounting for 0.1% - 0.5% of the total mass of the mixed resin), coat it on the surface of the main coating, and cure it by ultraviolet-light - hot air dual curing: ultraviolet wavelength 365 nm, irradiation intensity 300 - 600 mW / cm 2 Irradiate for 2 - 5 min, and then cure with hot air at 140 - 170 °C for 8 - 12 min to form an intermediate layer with a thickness of 6 - 12 μm; rapid cross-linking is initiated by ultraviolet light, internal stress is eliminated by hot air curing, the denseness of the intermediate layer is increased by more than 20%, and the curing efficiency is improved and the curing time is shortened by ultraviolet-light - hot air dual curing;
[0040] In this step, the azodiisobutyronitrile initiator can decompose under heat or ultraviolet light to generate free radicals, initiating graft copolymerization between the unsaturated double bonds in the fluorinated epoxy resin and the active hydrogen in the polyurethane resin to form a three-dimensional crosslinked network. By adding the azodiisobutyronitrile initiator, the network crosslinking density is enhanced and the curing time is shortened; the epoxy groups in the fluorinated epoxy resin react with the isocyanate groups or hydroxyl groups of the polyurethane during curing to form ether bonds or urethane bonds, enhancing the interfacial chemical bonding, improving the hydrophobicity, corrosion resistance, heat resistance of the coating, optimizing the high-frequency dielectric properties of the coating, and reducing the high-frequency loss.
[0041] 4) Coating of the outer layer: A blend of polyesterimide resin and polyphenylene sulfide (mass ratio 5 - 10:2 - 4) is used, and modified nano mica flakes (thickness ≤ 50 nm, aspect ratio ≥ 50) are added as the reinforcing phase. An outer layer with a thickness of 5 - 8 μm is formed by electrostatic atomization spraying process, the spraying voltage is 20 - 50 kV, and the curing conditions are 180 - 240 °C and circulating hot air curing for 20 - 40 min under nitrogen protection;
[0042] In this step, by adding polyphenylene sulfide and modified nano mica flakes, it is beneficial to reduce the dielectric loss. Blending the two with polyesterimide resin can improve the insulation performance, heat resistance, and thermal stability of the outer layer;
[0043] The modified nano mica flakes are nano mica flakes modified by ionic liquids. The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, etc. The addition amount of the ionic liquid is 1% - 3% of the mass of the nano mica flakes. By adding the modified nano mica flakes, its dispersibility in the resin is enhanced, the compatibility with the resin is improved, and the mechanical strength of the coating is increased, providing support for the performance improvement of the high-frequency insulating coating.
[0044] 5) Post-treatment: Laser polishing treatment is carried out on the coating surface. The laser wavelength is 1064 nm, the power density is 10 - 25 J / cm 2 , and the scanning speed is 100 - 200 mm / s, so that the surface roughness Ra of the coating ≤ 0.1 μm. In this step, laser polishing is used to reduce the electric field concentration caused by surface defects.
[0045] To improve the protection level of the enameled wire and reduce the friction coefficient, the present invention can also select to perform step 6) after step 50) according to actual needs: A PFPE protective film with a thickness of 0.5 - 2 μm is coated on the outer layer surface by supercritical CO2-assisted deposition technology, the pressure is 8 - 15 MPa, and the temperature is 40 °C - 70 °C. Whether step 6) is implemented or not completely depends on the actual needs of the user.
[0046] The present invention also discloses a high-frequency voltage-resistant enameled wire prepared by a method for manufacturing a high-frequency voltage-resistant enameled wire. The high-frequency voltage-resistant enameled wire includes a conductor and a main coating, an intermediate coating, and an outer layer sequentially coated on the outside of the conductor. The coating thickness of the main coating is 12-20 μm, the thickness of the intermediate coating is 6-12 μm, and the thickness of the outer layer is 5-8 μm.
[0047] Example 1
[0048] A method for manufacturing a high-frequency voltage-resistant enameled wire includes the following steps:
[0049] 1) Conductor pretreatment: The surface of the copper conductor is subjected to plasma etching treatment. The etching gas is a mixed gas of argon and oxygen (volume ratio 3:1), the etching power is 600 W, and the treatment time is 30 s, so that the surface roughness Ra of the copper conductor reaches 1.0 μm. Through the plasma etching technology in this step, the interfacial bonding force between the copper conductor and the subsequently formed coating can be enhanced, and the adhesion of the coating can be significantly improved, thus avoiding the occurrence of phenomena such as coating peeling.
[0050] 2) Main coating application: Polyimide resin and modified nano-fillers are blended at a weight ratio of 90:10 to form a composite coating material. After ultrasonic dispersion and homogenization, it is applied to the surface of the copper conductor, and the coating thickness is 15 μm. A stepped high-temperature curing process is used for curing:
[0051] The first stage: 240 °C, pre-curing for 6 min;
[0052] The second stage: 300 °C, final curing for 20 min;
[0053] In this step, the modified nano-filler has a particle size of 50 nm. The modified nano-filler is a mixture of nano-barium titanate particles and nano-titanium nitride particles modified by silane coupling agent KH550, and the mass ratio of nano-barium titanate particles to nano-titanium nitride particles is 1:2. In the present invention, polyimide resin is compounded with the modified nano-filler. Modification by silane coupling agent is beneficial to enhancing the interfacial bonding force between the modified nano-filler and polyimide resin, reducing particle agglomeration, reducing interfacial defects, improving the densification of the main coating, blocking moisture penetration, and preventing deterioration of dielectric properties caused by moisture absorption of the coating under high-frequency electric field. Polyimide resin has good high-temperature resistance and flexibility, but poor thermal conductivity. By compounding nano-titanium nitride particles with high thermal conductivity, high heat conductivity, and high conductive shielding, which are dispersed in polyimide resin as a heat conduction path, the overall thermal conductivity and high-temperature resistance of the main coating can be significantly improved, the Joule heat accumulation under high-frequency electric field can be reduced, the high-frequency eddy current loss can be reduced, and the synergistic effect of heat conduction and heat dissipation can be achieved. At the same time, the dielectric properties and mechanical properties can be optimized, the scratch resistance and wear resistance of the main coating can be improved, the formation of a conductive network can be avoided by nano-scale dispersion, the dielectric loss of the main coating can be significantly reduced, and the matching degree of the coating characteristic impedance with the copper conductor can be improved by dielectric regulation of nano-barium titanate particles, matching the high-frequency impedance, and reducing the electromagnetic wave reflection loss. By staged curing, the crystallinity of the main coating can be improved, and the interfacial bonding force can be enhanced by combining plasma etching technology.
[0054] 3) Intermediate coating application: Polyurethane resin and fluorinated epoxy resin (fluorine content 10%) are mixed at a mass ratio of 5:2 to obtain a mixed resin, and then azobisisobutyronitrile initiator (accounting for 0.1% of the total mass of the mixed resin) is added and applied on the surface of the main coating, and cured by ultraviolet-light - hot air dual curing: ultraviolet wavelength 365 nm, irradiation intensity 300 mW / cm 2 Irradiate for 5 min, and then cure with hot air at 170 °C for 8 min to form an intermediate layer with a thickness of 12 μm; rapid cross-linking is initiated by ultraviolet light, internal stress is eliminated by hot air curing, the densification of the intermediate layer is increased by more than 20%, and the curing efficiency is improved and the curing time is shortened by ultraviolet-light - hot air dual curing;
[0055] In this step, the azobisisobutyronitrile initiator can decompose under heat or ultraviolet light to generate free radicals, which initiate the graft copolymerization of the unsaturated double bonds in the fluorinated epoxy resin and the active hydrogen in the polyurethane resin to form a three-dimensional cross-linked network. By adding the azobisisobutyronitrile initiator, the network cross-linking density is enhanced and the curing time is shortened; the epoxy groups in the fluorinated epoxy resin react with the isocyanate groups or hydroxyl groups of the polyurethane during the curing process to form ether bonds or urethane bonds, enhancing the interfacial chemical bonding, improving the hydrophobicity, corrosion resistance, heat resistance of the coating, optimizing the high-frequency dielectric properties of the coating, and reducing the high-frequency loss.
[0056] 4) Outer coating application: A blend of polyesterimide resin and polyphenylene sulfide (mass ratio 5:2) is used, and modified nano mica flakes (thickness 50 nm, aspect ratio 50) are added as the reinforcing phase. An outer layer with a thickness of 8 μm is formed through an electrostatic atomization spraying process. The spraying voltage is 50 kV, and the curing conditions are 180 °C and circulating hot air curing for 40 min under nitrogen protection;
[0057] In this step, by adding polyphenylene sulfide and modified nano mica flakes, it is beneficial to reduce the dielectric loss. Blending the two with polyesterimide resin can improve the insulation performance, heat resistance, and thermal stability of the outer layer;
[0058] The modified nano mica flakes are nano mica flakes modified by ionic liquids. The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, etc. The addition amount of the ionic liquid is 1% of the mass of the nano mica flakes. By adding the modified nano mica flakes, its dispersibility in the resin is enhanced, the compatibility with the resin is improved, and the mechanical strength of the coating is increased, providing support for the performance improvement of the high-frequency insulation coating.
[0059] 5) Post-treatment: Laser polishing treatment is carried out on the coating surface. The laser wavelength is 1064 nm, the power density is 10 J / cm 2 , and the scanning speed is 100 mm / s to make the surface finish of the coating Ra = 0.1 μm. In this step, laser polishing is used to reduce the electric field concentration caused by surface defects.
[0060] Example 2
[0061] A manufacturing method of a high-frequency voltage resistant enameled wire includes the following steps:
[0062] 1) Conductor pretreatment: Plasma etching treatment is carried out on the surface of the copper conductor. The etching gas is a mixed gas of argon and oxygen (volume ratio 2:1), the etching power is 500 W, and the treatment time is 30 s to make the surface roughness Ra of the copper conductor reach 1.5 μm; In this step, through plasma etching technology, the interfacial bonding force between the copper conductor and the subsequently formed coating can be enhanced, significantly improving the adhesion of the coating, thus avoiding the occurrence of phenomena such as coating peeling.
[0063] 2) Main coating application: Polyimide resin and modified nano fillers are blended in a weight ratio of 92:8 to form a composite coating. After ultrasonic dispersion and homogenization, it is coated on the surface of the copper conductor, and the coating thickness is 12 μm. A stepped high-temperature curing process is used for curing:
[0064] The first stage: 260 °C, pre-curing for 2 min;
[0065] The second stage: 350 °C, final curing for 10 min;
[0066] In this step, the modified nano-fillers have a particle size of 90 nm, and the modified nano-fillers are a mixture of nano-barium titanate particles and nano-titanium nitride particles modified by a silane coupling agent. In the present invention, polyimide resin is compounded with the modified nano-fillers. Modification by a silane coupling agent is beneficial to enhancing the interfacial bonding force between the modified nano-fillers and the polyimide resin, reducing particle agglomeration, reducing interfacial defects, improving the densification of the main coating, blocking moisture penetration, and preventing deterioration of dielectric properties caused by moisture absorption of the coating under high-frequency electric fields. The polyimide resin has good high-temperature resistance and flexibility, but poor thermal conductivity. By compounding nano-titanium nitride particles with high thermal conductivity, high heat conductivity, and high conductive shielding, which are dispersed in the polyimide resin as heat conduction paths, the overall thermal conductivity and high-temperature resistance of the main coating can be significantly improved, the Joule heat accumulation under high-frequency electric fields can be reduced, the high-frequency eddy current loss can be reduced, and the synergistic effect of heat conduction and heat dissipation can be achieved. At the same time, the dielectric properties and mechanical properties can be optimized, the scratch resistance and wear resistance of the main coating can be improved, the formation of a conductive network can be avoided through nano-scale dispersion, the dielectric loss of the main coating can be significantly reduced, and the matching degree of the coating characteristic impedance with the copper conductor can be improved by dielectric regulation of nano-barium titanate particles, matching the high-frequency impedance, and reducing the electromagnetic wave reflection loss. The crystallinity of the main coating can be improved by staged curing, and the interfacial bonding force can be enhanced by combining with plasma etching technology.
[0067] 3) Intermediate coating application: Mix polyurethane resin and fluorinated epoxy resin (fluorine content 20%) in a mass ratio of 8:3 to obtain a mixed resin, and then add azobisisobutyronitrile initiator (accounting for 0.5% of the total mass of the mixed resin), and apply it on the surface of the main coating. Cure it by ultraviolet-light - hot air dual curing: ultraviolet wavelength 365 nm, irradiation intensity 600 mW / cm 2 Irradiate for 2 min, and then cure with hot air at 140 °C for 10 min to form an intermediate layer with a thickness of 10 μm; rapid cross-linking is initiated by ultraviolet light, and internal stress is eliminated by hot air curing, so that the densification of the intermediate layer is increased by more than 20%, and the curing efficiency is improved and the curing time is shortened by ultraviolet-light - hot air dual curing;
[0068] In this step, the azobisisobutyronitrile initiator can decompose under heat or ultraviolet light to generate free radicals, which initiate graft copolymerization between the unsaturated double bonds in the fluorinated epoxy resin and the active hydrogen in the polyurethane resin to form a three-dimensional cross-linked network. The network cross-linking density is enhanced by adding the azobisisobutyronitrile initiator, and the curing time is shortened; the epoxy groups in the fluorinated epoxy resin react with the isocyanate groups or hydroxyl groups of the polyurethane during curing to generate ether bonds or urethane bonds, enhancing the interfacial chemical bonding, improving the hydrophobicity, corrosion resistance, and heat resistance of the coating, optimizing the high-frequency dielectric properties of the coating, and reducing the high-frequency loss.
[0069] 4) Outer layer coating: A blend of polyesterimide resin and polyphenylene sulfide (mass ratio 10:2) is used, and modified nano mica flakes (thickness 50 nm, aspect ratio 50) are added as the reinforcing phase. An outer layer with a thickness of 7 μm is formed through an electrostatic atomization spraying process. The spraying voltage is 40 kV, and the curing conditions are 200 °C and circulating hot air curing for 30 min under nitrogen protection;
[0070] In this step, by adding polyphenylene sulfide and modified nano mica flakes, it is beneficial to reduce the dielectric loss. Blending the two with polyesterimide resin can improve the insulation performance, heat resistance, and thermal stability of the outer layer;
[0071] The modified nano mica flakes are nano mica flakes modified by ionic liquids. The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, etc. The addition amount of the ionic liquid is 3% of the mass of the nano mica flakes. By adding the modified nano mica flakes, its dispersibility in the resin is enhanced, the compatibility with the resin is improved, and the mechanical strength of the coating is increased, providing support for the performance improvement of the high-frequency insulation coating.
[0072] 5) Post-treatment: Laser polishing treatment is performed on the coating surface. The laser wavelength is 1064 nm, the power density is 15 J / cm 2 , and the scanning speed is 150 mm / s, so that the surface roughness Ra of the coating is 0.1 μm. In this step, laser polishing reduces the electric field concentration caused by surface defects.
[0073] 6) A PFPE protective film with a thickness of 2 μm is coated on the outer layer surface through a supercritical CO2-assisted deposition technique. The pressure is 15 MPa and the temperature is 70 °C, which improves the protection level of the enameled wire and reduces the friction coefficient.
[0074] The rest is the same as in Example 1.
[0075] Example 3
[0076] A method for manufacturing a high-frequency voltage-resistant enameled wire includes the following steps:
[0077] 1) Conductor pretreatment: The surface of the copper conductor is subjected to plasma etching treatment. The etching gas is a mixed gas of argon and oxygen (volume ratio 3:1). The etching power is 200 W, and the treatment time is 60 s, so that the surface roughness Ra of the copper conductor reaches 0.8 μm. In this step, the plasma etching technology can enhance the interfacial bonding force between the copper conductor and the subsequently formed coating, significantly improve the adhesion of the coating, and thus avoid the occurrence of phenomena such as coating peeling.
[0078] 2) Main coating application: A composite coating is formed by blending polyimide resin and modified nano fillers in a weight ratio of 80:20. After ultrasonic dispersion, it is coated on the surface of the copper conductor. The coating thickness is 20 μm, and a stepped high-temperature curing process is used for curing:
[0079] The first stage: 250 °C, pre-curing for 5 min;
[0080] The second stage: 320 °C, final curing for 16 min;
[0081] In this step, the particle size of the modified nano filler is 30 nm, and the modified nano filler is a mixture of nano barium titanate particles and nano titanium nitride particles modified by a silane coupling agent. In the present invention, polyimide resin is compounded with the modified nano filler. Modification by a silane coupling agent is beneficial to enhancing the interfacial bonding force between the modified nano filler and the polyimide resin, reducing particle agglomeration, reducing interfacial defects, improving the densification of the main coating, blocking moisture penetration, and preventing the deterioration of dielectric properties caused by moisture absorption of the coating under high-frequency electric fields. The polyimide resin has good high-temperature resistance and flexibility, but poor thermal conductivity. By compounding nano titanium nitride particles with high thermal conductivity, high heat conductivity, and high conductive shielding, which are dispersed in the polyimide resin as heat conduction paths, the overall thermal conductivity and high-temperature resistance of the main coating can be significantly improved, the Joule heat accumulation under high-frequency electric fields can be reduced, the high-frequency eddy current loss can be reduced, the synergistic effect of heat conduction and heat dissipation can be achieved, and at the same time, the dielectric properties and mechanical properties can be optimized, the scratch resistance and wear resistance of the main coating can be improved. By nano-level dispersion, the formation of a conductive network is avoided, and the dielectric loss of the main coating is significantly reduced. By dielectric regulation of nano barium titanate particles, the matching degree of the coating characteristic impedance with the copper conductor is improved, the high-frequency impedance is matched, and the electromagnetic wave reflection loss is reduced. By staged curing, the crystallinity of the main coating can be improved, and the interfacial bonding force can be enhanced by combining with plasma etching technology.
[0082] 3) Coating of the intermediate layer: Mix polyurethane resin and fluorine-containing epoxy resin (fluorine content 15%) at a mass ratio of 7:2 to obtain a mixed resin, and then add azobisisobutyronitrile initiator (accounting for 0.4% of the total mass of the mixed resin), and coat it on the surface of the main coating. Cure it by ultraviolet-light - hot air dual curing: ultraviolet wavelength 365 nm, irradiation intensity 400 mW / cm 2 Irradiate for 4 min, and then cure with hot air at 160 °C for 12 min to form an intermediate layer with a thickness of 7 μm; Rapid cross-linking is initiated by ultraviolet light, and internal stress is eliminated by hot air curing, so that the densification of the intermediate layer is increased by more than 20%. The curing efficiency is improved by ultraviolet-light - hot air dual curing, and the curing time is shortened;
[0083] In this step, the azodiisobutyronitrile initiator can decompose under heat or ultraviolet light to generate free radicals, initiating graft copolymerization between the unsaturated double bonds in the fluorinated epoxy resin and the active hydrogen in the polyurethane resin to form a three-dimensional crosslinked network. By adding the azodiisobutyronitrile initiator, the network crosslinking density is enhanced and the curing time is shortened. The epoxy groups in the fluorinated epoxy resin react with the isocyanate groups or hydroxyl groups of the polyurethane during curing to form ether bonds or urethane bonds, enhancing the interfacial chemical bonding, improving the hydrophobicity, corrosion resistance, and heat resistance of the coating, optimizing the high-frequency dielectric properties of the coating, and reducing the high-frequency loss.
[0084] 4) Coating of the outer layer: A blend of polyesterimide resin and polyphenylene sulfide (mass ratio 8:4) is used, and modified nano mica flakes (thickness 40 nm, aspect ratio 50) are added as the reinforcing phase. An outer layer with a thickness of 6 μm is formed through an electrostatic atomization spraying process. The spraying voltage is 25 kV, and the curing conditions are 240 °C and circulating hot air curing for 20 min under nitrogen protection.
[0085] In this step, by adding polyphenylene sulfide and modified nano mica flakes, it is beneficial to reduce the dielectric loss. Blending the two with polyesterimide resin can improve the insulation performance, heat resistance, and thermal stability of the outer layer.
[0086] The modified nano mica flakes are nano mica flakes modified by ionic liquids. The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, etc. The addition amount of the ionic liquid is 2% of the mass of the nano mica flakes. By adding the modified nano mica flakes, its dispersibility in the resin is enhanced, the compatibility with the resin is improved, and the mechanical strength of the coating is increased, providing support for the performance improvement of the high-frequency insulation coating.
[0087] 5) Post-treatment: Laser polishing treatment is performed on the coating surface. The laser wavelength is 1064 nm, the power density is 25 J / cm 2 , and the scanning speed is 190 mm / s, so that the surface roughness Ra of the coating is 0.08 μm. In this step, laser polishing is used to reduce the electric field concentration caused by surface defects.
[0088] The rest is the same as in Example 1.
[0089] For the parts or structures not specifically described in the present invention, existing technologies or existing products can be used, and no further elaboration will be made here.
[0090] The above are only the embodiments of the present invention, and thus do not limit the patent scope of the present invention. Any equivalent structural or equivalent process transformations made by using the content of the specification of the present invention, or directly or indirectly applied in other related technical fields, are similarly included in the patent protection scope of the present invention.
Claims
1. A manufacturing method of a high-frequency voltage resistant enameled wire, characterized in that, It includes the following steps: 1) Conductor pretreatment: performing plasma etching treatment on the surface of the conductor; 2) Coating the main coating on the surface of the conductor obtained in step 1) to form the main coating; 3) Coating the intermediate coating on the surface of the main coating obtained in step 2) to form the intermediate coating; 4) Coating the outer coating on the surface of the intermediate coating obtained in step 3) to form the outer layer; 5) Post-treatment: performing laser polishing treatment on the surface of the outer layer.
2. The manufacturing method of a high-frequency voltage resistant enameled wire according to claim 1, characterized in that, In step 1), the etching gas is a mixed gas of argon and oxygen with a volume ratio of 2 - 3:1, the etching power is 200 - 600 W, the treatment time is 20 - 60 s, so that the surface roughness Ra of the conductor reaches 0.6 - 1.5 μm.
3. The manufacturing method of a high-frequency voltage-resistant enameled wire according to claim 1, characterized in that, In step 2), the preparation raw materials of the main coating include the following components in parts by weight: 80 - 92 parts of polyimide resin; 8 - 20 parts of modified nano-fillers.
4. The manufacturing method of a high-frequency voltage-resistant enameled wire according to claim 3, characterized in that, The particle size of the modified nano-fillers is 20 - 90 nm, and the modified nano-fillers are a mixture of nano-barium titanate particles and nano-titanium nitride particles modified by a silane coupling agent.
5. The manufacturing method of a high-frequency voltage resistant enameled wire according to claim 3, characterized in that, In step 2), the steps of coating the main coating on the surface of the conductor obtained in step 1) to form the main coating include: Ultrasonically dispersing the polyimide resin and the modified nano-fillers evenly, then coating them on the surface of the conductor, with a coating thickness of 12 - 20 μm, and curing them by a stepped high-temperature curing process: The first stage: 240 - 260 °C, pre-curing for 2 - 6 min; The second stage: 300 - 350 °C, final curing for 10 - 20 min.
6. The manufacturing method of a high-frequency voltage resistant enameled wire according to claim 1, characterized in that, In step 3), the steps of coating the intermediate coating on the surface of the main coating obtained in step 2) to form the intermediate coating include: Mixing polyurethane resin and a fluorinated epoxy resin with a fluorine content of 10% - 20% evenly by a mass ratio of 5 - 8:2 - 3 to obtain a mixed resin, then adding an azobisisobutyronitrile initiator, continuing to mix evenly, coating it on the surface of the main coating, and curing it by an ultraviolet light - hot air double curing process: Ultraviolet wavelength 365 nm, irradiation intensity 300 - 600 mW / cm 2 Irradiate for 2 - 5 min, and then cure by hot air at 140 - 170 °C for 8 - 12 min to form an intermediate layer with a thickness of 6 - 12 μm.
7. The manufacturing method of a high-frequency voltage resistant enameled wire according to claim 1, characterized in that, In step 4), the steps of coating the outer coating on the surface of the intermediate coating obtained in step 3) to form the outer layer include: Mixing polyesterimide resin and polyphenylene sulfide evenly by a mass ratio of 5 - 10:2 - 4, adding modified nano-mica flakes as the reinforcing phase, forming an outer layer with a thickness of 5 - 8 μm by an electrostatic atomization spraying process, with a spraying voltage of 20 - 50 kV, and the curing conditions are 180 - 240 °C, circulating hot air curing for 20 - 40 min under nitrogen protection.
8. The manufacturing method of a high-frequency voltage resistant enameled wire according to claim 6, characterized in that, The thickness of the modified nano-mica flakes ≤ 50 nm, and the aspect ratio ≥ 50.
9. The manufacturing method of a high-frequency voltage-resistant enameled wire according to claim 1, characterized in that In step 5), the laser wavelength is 1064 nm, the power density is 10 - 25 J / cm 2 , the scanning speed is 100 - 200 mm / s, and the surface finish of the outer layer Ra ≤ 0.1 μm.
10. A high-frequency voltage-resistant enameled wire prepared by the method for manufacturing a high-frequency voltage-resistant enameled wire according to any one of claims 1 - 9.